Communication Strategies for Developing the Mount Rinjani Sembalun Tourist Destination, Lombok - Enza Dwi Wulandari; Sukarta Sukarta; Suhadah Suhadah (JURNAL ECONOMINA, 2026)
This study aims to examine communication strategies in the development of Mount Rinjani as a tourist destination via the Sembalun route in East Lombok by involving various stakeholders, namely tourism managers, hiking guides, local communities, vendors, and tourists. The study employs a descriptive qualitative approach with informants selected through purposive sampling. Data collection was conducted through in-depth interviews, field observations, and documentation. The data obtained were analyzed using the Miles and Huberman model, which encompasses data reduction, data presentation, and drawing conclusions, while data validity was tested through source and method triangulation. The results of the study indicate that communication strategies in the development of the Sembalun destination are implemented through the comprehensive dissemination of information regarding tourism potential, the utilization of social media as the primary promotional medium, and the application of interpersonal communication characterized by a friendly and familial approach. In addition to focusing on promotion, the communication strategy also emphasizes education, climbing safety, and the preservation of local cultural values. However, challenges remain, including weak communication coordination among stakeholders and low levels of community involvement in formal tourism development programs. Therefore, there is a need to strengthen communication strategies that are more collaborative, participatory, and sustainable in order to enhance the image and competitiveness of Sembalun as a tourist destination